The Tendency of Conduct Disorder in Terms of Authoritarian Parenting and Gender - Harkina, Prida; Sandayanti, Vira; Supriyati, Supriyati (ANFUSINA: Journal of Psychology, 2024)
Lampung Province has a rather high crime rate, particularly since most of these criminals are still in adolescence. Teenagers who engage in such criminal action are more likely to repeat the act, which might be categorized as a conduct disorder tendency. This research aims to investigate the relationship between authoritarian parenting and conduct disorder. The sampling technique employed was cluster sampling, with 395 high school students from science and social studies majors in the tenth, eleventh, and twelfth grades in Bandar Lampung. The research instruments included a conduct disorder tendency questionnaire, an authoritarian parenting questionnaire, and demographic data, such as student gender. The data analysis comprised multiple linear regression. The findings of statistical analysis show that authoritarian parenting and gender have an impact on the probability of conduct disorder. These findings emphasize the importance of considering parents' roles and approaches while raising children and adolescents. This research is expected to be useful in developing more successful family education interventions or programs, particularly in increasing the dynamics and quality of relationships between parents and children or adolescents.Keywords: Tendency of conduct disorder, authoritarian parenting, gender